METODE INTERPOLASI DATA SESUAI POLA SINUSOIDAL PADA SINOGRAM TOMOGRAFI KOMPUTER - , I Gede Arya Wiguna ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A method of data interpolation based on a sinusoidal pattern of computed tomography sinogram has been developed. This method was used to interpolate sonogram data of an object with an angle scanning of 5 o , 8 o , 10 o , 15 o , and 20 o . In sinogram interpolation result performed sinogram data correction process. The sinogram data has been corrected then reconstraction performed to obtain crosssectional object. Image reconstruction results were analyzed statistically and numerically. Statistical analysis was done by calculating the coefficient correlation image, while the numerical analysis is done by calculating the value of the mean square difference (rmsd) and maximum error (Emax) from the image. The results obtained that a method has been able to interpolate the data sinogram of limited projection data into a sinogram complete projection data. This method is good enough to used interpolate the data sinogram homogeneous with a minimal amount of 36 data projection (from a total of 360 projection data). This interpolation method hasânt been able to interpolate unhomogeneous data sinogram. The calculation of the correlation coefficient obtained largest value from the cylindrical object 0.9975 and the smallest is module 0.7155, value of the correlation coefficient rectangle object and triangle object are 0.9861 and 0.9287 respectively. Value from calculation of rmsd and Emax obtained a cylinder object have a rmsd and Emax values the least 3.76% and 44.25%, while the module object object had a rmsd and Emax value the greatest 17.94% and 93.14%. Rmsd and Emax values on the object rectangle and triangle object are 4.72% and 83.79% , 3.85% and 64.12% respectively. From the calculation of the correlation coefficient, rmsd and Emax value interpolation of cylindrical objects produced the most good, it is because the cylindrical object has a sinogram data most homogeneous and the most simple pattern sinogram.